1977
DOI: 10.1002/hlca.19770600627
|View full text |Cite
|
Sign up to set email alerts
|

Stoffwechselprodukte von Mikroorganismen 6‐Chlorgenistein und 6,3′‐Dichlorgenistein. 164. Mitteilung

Abstract: Metabolites from Microorganisms. 6-Chlorogenistein and 6,3'-Dichlorogenistein SummaryA strain of Streptomyces griseus produced chlorinated metabolites in media containing soybean meal. Two of these metabolites were isolated together with a chlorine free compound which could be identified as the isoflavone genistein (I) by its spectral properties and by comparison with an authentic sample. By NMR. and mass spectroscopy the chlorinated compounds were shown to be 6-chlorogenistein (TI) and 6,3'-dichlorogenistein … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

1977
1977
2019
2019

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(5 citation statements)
references
References 5 publications
(4 reference statements)
0
5
0
Order By: Relevance
“…This process dramatically reduced the dataset complexity, leaving <200 unique ions from an original set of ∼3000. Manual curation showed that most of the remaining ions corresponded to halogenated molecules (based on isotope patterns), leaving twelve previously identified fasamycin and formicamycin congeners, two additional fasamycin/formicamycin congeners that remain uncharacterized due to trace levels, and the known isoflavone 6-chlorogenistein 11 (Supplementary Note 1 and Supplementary Figs. 11–14) along with a regioisomer.…”
Section: Resultsmentioning
confidence: 99%
“…This process dramatically reduced the dataset complexity, leaving <200 unique ions from an original set of ∼3000. Manual curation showed that most of the remaining ions corresponded to halogenated molecules (based on isotope patterns), leaving twelve previously identified fasamycin and formicamycin congeners, two additional fasamycin/formicamycin congeners that remain uncharacterized due to trace levels, and the known isoflavone 6-chlorogenistein 11 (Supplementary Note 1 and Supplementary Figs. 11–14) along with a regioisomer.…”
Section: Resultsmentioning
confidence: 99%
“…Funayama et al (21) used long-range selective proton decoupling (LSPD) experiments to make a similar assignment for 8-chloro-3',4',5',7-tetrahydroxyisoflavone, which was isolated from a streptomycete grown on soybean-containing medium. Kónig et al (22) claimed to isolate 6-chlorogenistein from fermentations of S. griseus grown in a soybean-meal containing medium. However, structural assignments were based largely on the proximity of the single A ring proton signal at 6.50 ppm to the H-8 proton of 1 which resonates at 6.42 ppm, and were not confirmed by necessary proton-carbon correlation techniques such as HMBC or LSPD.…”
Section: Resultsmentioning
confidence: 99%
“…Although 2 and 3 are new compounds, there have been two other reports (21,22) of chlorinated isoflavonoids being isolated from streptomycetes grown on soybean-meal containing media. These compounds were 6-chlorogenistein, 6,3-dichlorogenistein, and 8-chloro-3' ,4', 5,7-tetrahydroxyisoflavone.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Bacterial strains, culture conditions, and vectors Streptomyces albogriseolus MJ286-76F7 was cultured in soybean flour Ámannitol medium (Kö nig et al 1977) at 278C for 3 days with shaking at 160 rpm. Overnight cultures of Escherichia coli TG1 (Gibson 1984), E. coli BL21(DE3)pLysS (Invitrogen), and E. coli S17-1 (Simon et al 1983) were grown in HNB medium (Wynands & van Pée 2004) at 378C.…”
Section: Methodsmentioning
confidence: 99%